Library use : A handbook for psychology - Reed, Jeffrey G. (American Psychological Association, 2003)
Newly revised and updated, this handbook is a guide for students to the resources available in the library and how to use them. It covers topic selection and definition, books and periodicals, indexing and abstracting tools, psychological tests and measures, and other resources as they relate to psychology. New features in the second edition include discussion of CD-ROM [compact disk-read only memory] technology, new handouts and other sources, and how to locate books and chapters in "Psychological Abstracts." Interesting and relevant sample topics are used throughout for illustration.